Analisis Tingkat Kesehatan Koperasi Berdasarkan Perdep Kementerian Koperasi dan Usaha Kecil Menengah Nomor 06/Per/Dep.6/IV/2016 - Ilyas Nur Shiddiq; Arwan Gunawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Health level analysis is needed to assist development. The Mitra Sejahtera Credit Cooperative in 2018 - 2020 has not been assessed so that its health is not yet known. If, after the analysis, it is found that the inhibiting factors can be used as suggestions and input. The purpose of this study was to analyze the health level of Mitra Sejahtera Credit Cooperatives based on the Ministry of Cooperatives and Small and Medium Enterprises Decree Number 06/Per/Dep.6/IV/2016. The method used in this research is descriptive qualitative method with data collection techniques, documentation and interviews. This research shows different results in every aspect, there are aspects that are already good and still need to be improved. Overall, the results of the study show that the Mitra Sejahtera Credit Cooperative in 2018 and 2019 was in the fairly healthy category because it obtained scores of 71.60 and 72.60, respectively. Whereas in 2020 it obtained a score of 64.40 so it was in the category under supervision.